PROSES PERALIHAN HAK ATAS TANAH MELALUI JUAL BELI DITINJAU DARI PERBEDAAN IDENTITAS PEMEGANG HAKDI KABUPATEN WONOGIRI - CAHYONOWINAHYU, BUDI HARSOYO (Dinamika Hukum, 2019)
The purpose of this research is to know the process of registering the transfer of rights over land at the onogiri District Land Office if the identity of the holder of the land rights has a difference between what is written in the certificate of land rights and what is written on the identity card. faced by the Wonogiri Regency Land Office, and the solutions taken to deal with these problems. Legal research used is descriptive research and when viewed from its type, it includes empirical research using a qualitative approach. Research location in Wonogiri Regency. The types of data and data sources used are primary data and secondary data. The data collection technique used is library research both from books, legislation, documents, and so on, and through observation (interview) and interviews (interviews). Data analysis techniques use an interactive analysis model. The results of this research, first, the procedure for the transfer of land rights through buying and selling in Wonogiri Regency is in accordance with Government Regulation Number 24 of 1997 concerning Land Registration. The procedure for transferring land rights through buying and selling based on Government Regulation Number 24 of 1997 must fulfill formal material requirements and requirements. The material requirements cover the subject and object of the rights to be traded, while the formal terms of sale and purchase of land rights must be proven by a sale and purchase deed (AJB) made by or in the presence of a Land Deed Officer. Second, the constraints in the implementation of the transfer of land rights through buying and selling due to differences in the identity of rights holders include the culture of people who easily change names, require a relatively longer process due to additional requirements that must be fulfilled, namely by making a witness application by witnesses and known by the Village Head and the local Sub-District Head. Third, the solution is to provide clear criteria in a statutory regulation so that it does not cause a different understanding or meaning in determining the resolution of the problem of changing names. Keywords: Transition of Land Rights; Buy and sell of Land; Change name.